2017
DOI: 10.1183/16000617.0040-2017
|View full text |Cite
|
Sign up to set email alerts
|

Is mitochondrial dysfunction a driving mechanism linking COPD to nonsmall cell lung carcinoma?

Abstract: Chronic obstructive pulmonary disease (COPD) patients are at increased risk of developing nonsmall cell lung carcinoma, irrespective of their smoking history. Although the mechanisms behind this observation are not clear, established drivers of carcinogenesis in COPD include oxidative stress and sustained chronic inflammation. Mitochondria are critical in these two processes and recent evidence links increased oxidative stress in COPD patients to mitochondrial damage. We therefore postulate that mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 128 publications
(144 reference statements)
0
21
0
Order By: Relevance
“…The stressors leading to senescence include telomere shortening due to replicative exhaustion, DNA or chromatin structure and mitochondrial dysfunction [15][16][17][18][19]. Recent reports indicated that mitochondrial dysfunction plays an important role in initiating inflammatory responses and cellular senescence and has significance in the pathogenesis of lung disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…The stressors leading to senescence include telomere shortening due to replicative exhaustion, DNA or chromatin structure and mitochondrial dysfunction [15][16][17][18][19]. Recent reports indicated that mitochondrial dysfunction plays an important role in initiating inflammatory responses and cellular senescence and has significance in the pathogenesis of lung disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…Roles for urokinase plasminogen activation receptor (uPAR) in modulating EMT and direct associations between uPAR and vimentin expression in were also suggested (37). Mitochondrial dysfunction can also lead to EMT in smokers and COPD, hence cancer (38).…”
Section: Emt In Copdmentioning
confidence: 99%
“…In general, autophagy is regarded as a safety mechanism counteracting hyperactivation of inflammasomes and chronic inflammation-induced cancer [12]. Defects in canonical autophagy or mitophagy can lead to pathological responses and necrosis, promoting chronic inflammation and tumorigenesis [12,13]. Additionally, autophagy levels have been associated with cell death fate and cell clearance [12].…”
Section: Introductionmentioning
confidence: 99%